Clustering of Spontaneous Recurrent Seizures in a Mouse Model of Extended Hippocampal Kindling - Liu, Haiyu; Zhang, Liang (Frontiers in Neurology, 2021)
Patients with epilepsy often experience seizure clusters in which repetitive seizures occur with shorter than ordinary inter-seizure periods. Untreated seizure clusters are associated with high risks of status epilepticus, hospital admissions, and increased morbidity and mortality. Accumulating evidence indicates that occurrence of epileptic seizures exhibits rhythmic patterns at multiple timescales. Spontaneous recurrent seizures (SRS) observed from animal models of epilepsy also present clustering and/or rhythmic patterns. Electrical kindling of a limbic structure is a commonly used model of temporal lobe epilepsy. While classic kindling in a few weeks does not generally induce SRS, extended kindling over a few months can induce SRS in several animal species. SRS in kindled cats and monkeys were found to occur predominantly during sleep and often appear in cluster. It is currently unknown whether SRS in extended kindled rodents present similar patterns. We explored this by examining SRS in a mouse model of extended hippocampal kindling. Adult male mice (C57BL/6) experienced twice daily hippocampal stimulations and underwent continuous 24-hour EEG-video after ≥80 stimulations. SRS were recognized by EEG discharges and associated motor seizures. SRS were observed mainly while mice were in sleep or stable immobility. Inter-seizure intervals were of 10-120 min for most SRS events, and SRS intervals were not strongly correlated with EEG discharge durations or motor seizure severity scores. In addition, SRS with weak convulsive behaviors and more frequent appearance (up to 25 events/hour) were observed from some mice. These observations suggest seizure clustering a main feature of SRS in extended kindled mice. Experimental factors and circadian-related homeostatic mechanisms that may influence/underlie such clustering SRS are discussed.